Technological innovations and the expected demand for skilled labour at the firm level - Martin Falk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper analyses the link between technological product and processes innovations and expectations about future employment for different types of labour in manufacturing. The empirical model allows for endogeneity of the firm?s innovation decision in the labour demand equations. The system of probit equations is estimated using simulated ML based on 800 West German firms. The empirical evidence for dierent measures of technological innovations indicates that introduction of new market products is more important than any other measure of product innovation in determining the expected employment probabilities for homogeneous labour. Furthermore, as expected, technological innovations have the strongest impact on university graduates. Joint implementation of new products and new processes have a stronger impact on the employment expectations of university graduates than product innovations alone. Labour quality and turnover growth are also important factors of employment growth. Finally, tests of the exogeneity assumption of new market products in the labour demand equations can not be rejected.
Keywords: L8; J23; O33; 330; labour demand; product and process innovations; R&D; educational qualification structure; manufacturing; Industrielle Beschäftigung; Innovation; Technischer Fortschritt; Arbeitsnachfrage; Humankapital; Qualifikation; Hochqualifizierte Arbeitskräfte; Schätzung; Deutschland